Exploring the intersection of African Religion and the scientific method: A geographical perspective - Ochieng’, Richard; Tanui, Martin K. (Nairobi Journal of Humanities and Social Sciences, 2024)
In this paper, the authors delves into the intricate relationship between African religion and the scientific method, within the broader context of the African worldview. Religion, characterized by beliefs and practices concerning the supernatural, and the scientific method, a systematic approach to empirical inquiry, are often perceived as distinct paradigms. However, through examples from African cultures and traditions, the paper demonstrates how these seemingly disparate domains intersect and inform one another. By examining the geographical dimensions of African religious practices and scientific inquiry, the paper elucidates the inseparability of religion and science within the African context.